2006
DOI: 10.1248/bpb.29.855
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil Fat Emulsion to Prevent TPN-Induced Liver Damage: Possible Molecular Mechanisms and Clinical Implications

Abstract: INTRODUCTIONTotal parenteral nutrition (TPN), which is recognized as one method for parenteral hyperalimentation, has been found to be an effective and relatively safe method for supplying energy and nutrients to surgical patients. Following improvements in parenteral regimens including vitamins and trace elements and in catheter techniques to reduce the septic complications associated with TPN, TPN has been widely employed to provide complete nutritional support and therapeutic benefits in a variety of pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…However, forced administration of high glucose, as in fat-free TPN, caused fatty liver, as previously reported by Oshita et al (2004). Further, Nishimura et al (2006) recently reported that high serum glucose during the administration of fat-free TPN in infant rats decreased gluconeogenesis-and lipolysis-related gene expression in the liver but increased the expression of acetylcoenzyme A carboxylase (ACC), a key enzyme in lipogenesis, resulting in the accumulation of lipids in the liver. On the other hand, despite the fatty liver, serum lipid concentrations were significantly lower in the fat-free TPN group.…”
Section: Resultssupporting
confidence: 61%
“…However, forced administration of high glucose, as in fat-free TPN, caused fatty liver, as previously reported by Oshita et al (2004). Further, Nishimura et al (2006) recently reported that high serum glucose during the administration of fat-free TPN in infant rats decreased gluconeogenesis-and lipolysis-related gene expression in the liver but increased the expression of acetylcoenzyme A carboxylase (ACC), a key enzyme in lipogenesis, resulting in the accumulation of lipids in the liver. On the other hand, despite the fatty liver, serum lipid concentrations were significantly lower in the fat-free TPN group.…”
Section: Resultssupporting
confidence: 61%
“…In addition, stigmasterol, a soy-derived lipid, antagonizes FXR activity [47]. Interestingly, the addition of soybean fat emulsion prevents hepatic injury by TPN possibly by stimulating PPARα [48]. Notably, intensive insulin therapy reduces cholestasis and biliary sludge in critically ill patients [49], which may be linked to regulation of FXR expression by glucose [50].…”
Section: Role Of Bile Acid Transporters In Cholestasis – Pathophysiolmentioning
confidence: 99%
“…The study of Gura et al provides data, which allow the interpretation that PNLD potentially can be reversed when continuing parenteral soybean-based lipid solutions. Furthermore, animal studies have shown reversal of cholestasis using soybean oil (6,24). However, our observation of increased γ GT levels in the group receiving soybean-based lipids, and the growing evidence of clinical trials showing reversal of cholastasis (bilirubin and γ GT) support the conclusion of the beneficial effects of fish oil or fish oil-containing lipid solutions on PNLD.…”
Section: Discussionmentioning
confidence: 67%